Penanggulangan Tindak Pidana Pembuangan Bayi di Wilayah Hukum Polres Bireun - Nurjannah; Johari; Husni (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2023)
The legal issue in this study is to find out the factors that led to the occurrence of the crime of disposal of babies according to the perspective of criminal law, and to find out the obstacles and efforts to deal with the crime of disposal of babies in the jurisdiction of the Bireuen Police. Based on the results of the research, it shows that the causes of the crime of disposal of babies are promiscuity, free internet access, economic factors, lack of religious knowledge and lack of understanding of the law. Efforts that can be made by law enforcement officials to prevent the crime of disposal of babies from occurring are carried out through pre-emptive, preventive and repressive efforts aimed at reducing the number of cases of crime of disposal of babies